Clinical outcomes and risk factors for local residual/recurrent tumors after endoscopic submucosal dissection including major papilla for laterally spreading ampullary tumors - Naohisa Yahagi; Teppei Akimoto; Yusaku Takatori; Motoki Sasaki; Kurato Miyazaki; Atsuto Kayashima; Teppei Masunaga; Kumiko Kirita; Mari Mizutani; Hiroki Tamagawa; Shintaro Kawasaki; Takashi Seino; et al. (Endoscopy, 2026)
Background and study aims: Endoscopic papillectomy (EP) enables resection of ampullary lesions but is limited by piecemeal resection and high recurrence rates. To overcome these limitations, we developed endoscopic submucosal dissection including papilla (ESDIP). This study aimed to evaluate clinical outcomes and identify risk factors for local residual/recurrent tumor after ESDIP for laterally spreading ampullary tumors. Patients and methods: This single-center retrospective study analyzed consecutive patients who underwent ESDIP between 2011 and 2024. The primary outcome was local residual/recurrent tumor after ESDIP. Risk factors for local residual/recurrent tumor were evaluated using Cox proportional hazards regression analysis. Results: Of the 81 consecutive patients in whom ESDIP was attempted, three were converted to EP or surgery. En bloc resection was achieved in all 78 patients. After excluding 23 patients based on the predefined exclusion criteria, 55 patients were analyzed. The median tumor size was 38 mm (range, 15-128 mm). Negative horizontal and vertical margins, excluding the papillary ductal margin (PM), were achieved in 48 patients (87%), whereas negative PM and R0 resection were achieved in 34 patients (62%) and 29 patients (53%), respectively. Median follow-up was 31 months. The 3-year cumulative incidence of residual/recurrent tumor was 33%, and all residual/recurrent tumors were confined to the papilla. Positive/indeterminate PM was a significant risk factor for local residual/recurrent tumor (hazard ratio, 8.35; 95% confidence interval, 2.35-29.64). Conclusions: Although ESDIP enabled en bloc resection of laterally spreading ampullary tumors, the high rate of positive/indeterminate PM, resulting in frequent papilla-confined residual/recurrent tumors, remained its main limitation.